Job Traits, Career Satisfaction and Future Intention: new evidence from Cyprus - Zopiatis, Anastasios; Theocharous, Antonis L.; Constanti, Panayiotis; Papadopoulos, Constantinos (My University, 2015)
Job satisfaction is probably one of the most researched topics in hospitality and tourism literature. Scholars have invested considerable resources in investigating this topic from an array of different perspectives with the intention of enhancing our conceptual understanding of the defining elements that affect employees’ satisfaction in the workplace. In contrast career satisfaction, defined as “…the individual’s satisfaction with the accumulation of their career-related experiences” (Dacre-Pool and Qualter, 2013, p. 216), has received much less attention. According to Heslin (2005) being satisfied with one’s career is the most usual manner in which to operationalize career success which in itself is a subjective state (De Vos and Soens, 2008). Laschinger (2012), by exploring employees’ job and career satisfaction, concludes that both are significantly associated to a variety of workforce conditions, including future career turnover behaviors and intentions.
Keywords: tourism; Future Intention; Job Traits; Career Satisfaction